2020
DOI: 10.2196/preprints.24186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiomyocyte Injury Following Acute Ischemic Stroke: Protocol for a Prospective Observational Cohort Study (Preprint)

Abstract: BACKGROUND Elevated cardiac troponin (cTn) indicating cardiomyocyte injury is common after acute ischemic stroke (AIS) and associated with poor functional outcome. Myocardial injury is part of a broad spectrum of cardiac complications that may occur after AIS. Previous studies have shown that in most patients the underlying mechanism of stroke-associated myocardial injury may not be a concomitant acute coronary syndrome. Evidence from animal research, clinical and neuroimaging studies s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Apart from acute thrombotic CAD, a mismatch of oxygen supply and demand is considered as a potential reason for increased troponin levels. Various other factors such as rhythm disturbances, blood pressure instabilities, respiratory failure and renal failure may also contribute to a rise in troponin levels (6). In our study, 13 out of 25 patients (52%) demonstrated (mainly focal) myocardial scars (LGE) with an overall low total volume of 5% LV mass, Tables 1, 2 and Supplementary Tables A, B.…”
Section: Myocardial Tissue Characterization By Comprehensive Cardiova...mentioning
confidence: 53%
See 4 more Smart Citations
“…Apart from acute thrombotic CAD, a mismatch of oxygen supply and demand is considered as a potential reason for increased troponin levels. Various other factors such as rhythm disturbances, blood pressure instabilities, respiratory failure and renal failure may also contribute to a rise in troponin levels (6). In our study, 13 out of 25 patients (52%) demonstrated (mainly focal) myocardial scars (LGE) with an overall low total volume of 5% LV mass, Tables 1, 2 and Supplementary Tables A, B.…”
Section: Myocardial Tissue Characterization By Comprehensive Cardiova...mentioning
confidence: 53%
“…Twenty-five complete datasets remained fully evaluable for this study. According to the fourth universal definition of myocardial infarction, patients were categorized 10.3389/fcvm.2022.989376 by their repeated troponin measurements in: (1) chronic myocardial injury (increased but stable troponin levels in terms of rise/fall ≤ 20% in serial measurements), and (2) acute myocardial injury (rise/fall of troponin > 20% in serial measurements) (6,7). Twelve healthy volunteers [5 female (42%), age 51 ± 9 years] served as a control group to define reference values for the CMR mapping sequences (T1 and T2 mapping).…”
Section: Patient Populationmentioning
confidence: 99%
See 3 more Smart Citations